Increasing the loading rate of continuous stirred tank reactor for coffee husk and pulp: Effect of trace elements supplement. Issue 8 (6th April 2018) - Chala, Bilhate; Oechsner, Hans; Fritz, Thomas; Latif, Sajid; Müller, Joachim
Abstract: In this study, the anaerobic performance and stability of coffee husk and pulp with and without trace element (TE) supplement was investigated, using 20 L mesophilic continuous stirred tank reactors for 140 days of experiment (DOE). The TE was cocktail of trace metals composed of Fe, Ni, Zn, Co, Mn, Mo, Se W and B. The organic loading rate (OLR) was increased stepwise from 2.5 (HRT = 40 d) to 6.0 kg VS m −3 d − 1 (HRT = 16.7 d). The highest methane productivity from pulp with and without TE was 1.272 and 0.965 m 3 m −3 d −1 at an OLR of 6.0 and 5.0 kg VS m −3 d −1 ; while the husks performed 0.895 and 0.795 m 3 m −3 d −1 respectively, both at an OLR of 6.0 kg VS m −3 d −1 . The specific methane yield (SMY) of pulp (at OLR = 5 kg VS m −3 d −1 ) with and without TEs was 217.9 ± 4.7 and 193.1 ± 8.2 L kg −1 VS; while husk yielded 149.2 ± 6.0 and 132.5 ± 4.9 L kg −1 VS, respectively. The effect of TEs on SMY was statistically significant (p < 001) at higher OLRs (5.0 ‐ 6.0 kg VS m −3 d −1 ). The TEs improved the anaerobic stability through an optimum alkalinity ratio (VFA/TIC < 0.3) and suppressed the accumulation of volatile fatty acids. Mono digestion of husks and pulp are prone to lack Mo, Zn, Ni and Fe in long‐term anaerobic fermentation. Further studies on co‐digestion of husk/pulp with animal manure and dry fermentation helps to efficiently use this biomass resource.